Observed gust wind speeds in the coterminous United States, and their relationship to local and regional drivers. Issue 173 (February 2018) - Letson, F.; Pryor, S.C.; Barthelmie, R.J.; Hu, W.
Abstract: Given the importance of wind gusts to structural design and the economic and ecological impacts of extreme winds, there is a need for better understanding of the spatial variability of wind gusts. Sonic anemometer wind measurements at 10-m a.g.l. from 801 US National Weather Service Automated Surface Observation System sites are used to characterize gust climates across the coterminous United States. These data indicate substantial regional and sub-regional variability across a range of gust metrics. For example, the locally-determined 95th percentile gust values exceed 16.46 ms -1 at most sites throughout the central plains, but are below 14.40 ms -1 throughout almost all of the southeastern stations. When site-specific gust metrics are conditionally sampled by the likelihood of deep convection and frequency of extra-tropical cyclones, the results indicate that gust factors tend to be lower in regions with higher convective potential, and higher in areas with a higher frequency of extra-tropical cyclones. Conversely, 1 and 10-year return period gusts are higher in the region with high convective potential, but do not exhibit consistently higher values in regions with a high frequency of extra-tropical cyclones. Terrain complexity and higher surface roughness are also found to increase gust factors but not absolute gust magnitudes. Highlights: Sonic anemometer data are used to characterize gusts at 801 sites in the US. Gust characteristics examined with respect to local and regional gust drivers. Intense gust magnitudes exhibit regional coherence. Extreme gusts and gust factors show more sub-regional variability. Sub-regional variability in gusts is underrepresented by current gust assessments.